Analisis Laporan Keuangan Perbandingan Kinerja Keuangan Perusahaan Sektor Perdagangan di Indonesia (Studi pada PT. Alfamidi PT. Alfamart PT. Indofood PT. Hero Supermarket Periode 2019-2023) - Maulana Ikhrom Ababil; Mochammad Nuruddin R; Sudarynianto NS; Paulino da Costa Ferreira; Cholis Hidayati (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This research aims to analyze the financial performance of trade sector companies in Indonesia, specifically PT. Alfamidi, PT. Alfamart, PT. Indofood, and PT. Hero Supermarket, in the period 2019-2023. This study uses a variety of financial ratios as a measuring instrument for assessing company performance, such as liquidity ratios (current ratios and quick ratios), activity ratios (receiving receivables, inventory, and fixed assets), and profitability ratios (profit margins, returns on assets, and return on equity). Through comparison of these ratios, this study aims to provide a comprehensive picture of the efficiency, profitability, and financial stability of each company. The results of the analysis show that PT. Hero Supermarket has a relatively superior performance in terms of return on equity (ROE) and return on assets (ROA), while PT. Indofood faces challenges in maintaining profitability and asset efficiency. PT. Alfamidi and PT. Alfamart showed stable performance even though he still had room for improvement in operational efficiency. This finding provides useful insights for stakeholders in making investment decisions as well as for these companies in formulating better financial management strategies in the future.